2017
DOI: 10.3390/molecules22040629
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Cordycepin Therapy Prolongs Survival of Oral Cancer-Bearing Mice and Inhibits Epithelial-Mesenchymal Transition

Abstract: Cordycepin (3′-deoxyadenosine) is a natural compound abundantly found in Cordyceps sinesis in natural and fermented sources. In this study, we examined the effects of cordycepin in a human oral squamous cell carcinoma (OSCC) xenograft model. Cordycepin was administered in a regular, low-dose and prolonged schedule metronomic therapy. Two doses of cordycepin (25 mg/kg, 50 mg/kg) were administrated five days a week for eight consecutive weeks. The tumor volumes were reduced and survival time was significantly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…1 ), but it did show anti-inflammatory activity. Previous studies have shown that cordycepin has anti-cancer effects in human breast cancer cells ( 29 ), human lung cancer cells ( 30 ), oral squamous cell carcinoma ( 31 ), and human bladder cancer cells ( 32 ). Cordycepin has also been shown to have anti-cancer effects in human colorectal cancer cells, but there have been few reports on cordycepin’s role in altering early events (i.e., migration and invasion) to prevent the progression into cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), but it did show anti-inflammatory activity. Previous studies have shown that cordycepin has anti-cancer effects in human breast cancer cells ( 29 ), human lung cancer cells ( 30 ), oral squamous cell carcinoma ( 31 ), and human bladder cancer cells ( 32 ). Cordycepin has also been shown to have anti-cancer effects in human colorectal cancer cells, but there have been few reports on cordycepin’s role in altering early events (i.e., migration and invasion) to prevent the progression into cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Integrin β1 can induce cancer cell migration (19), and it was found that the protein level of integrin β1 was also reduced in the Jam3 siRNA group, compared with that in the control group (P<0.05; Fig. 4A).…”
Section: Effects Of Jam3 On E-cadherin N-cadherin Integrin β1 Mmp-mentioning
confidence: 93%
“…Cordycepin (25-100 µM) can inhibit cancer stemness of TGF-induced chemo-resistant ovarian cancer cells [137]. Metronomic cordycepin therapy (25 mg/kg and 50 mg/kg) can prolong the survival of oral cancer-bearing mice and it (50 µM) inhibit EMT [138]. Cordycepin (100-200 µM) suppresses integrin/FAK signaling and EMT in HCC [139].…”
Section: Reversal Of Emt By Anti-inflammatory Natural Compoundsmentioning
confidence: 99%